Evaluating wild Turkey movement ecology: An example using first‐passage time analysis - Michael E. Byrne; Joshua D. Guthrie; Jason Hardin; Bret A. Collier; Michael J. Chamberlain (Wildlife Society Bulletin)
ABSTRACT Recent advances in animal tracking technology have increased interest in the field of animal movement ecology. Numerous methods have been developed to extract information from animal movement paths that can be used to link movement behavior to external stimuli such as habitat and climatic conditions. Given the recent development of Global Positioning System (GPS) technology suitable for use on wild turkeys (Meleagris gallapavo), we advocate the adoption of new methodologies to design novel research on wild turkey ecology. Here we provide a worked example using first‐passage time on male Rio Grande wild turkeys (M. g. intermedia) tracked via GPS in South Texas, USA, during April 2009 to illustrate one methodological option on which research can be based. From our example, we infer behavioral decisions in response to habitat variables that varied during the diurnal cycle; turkeys were more likely to exhibit localized movements during midday in open areas near food and water resources. We contend that by taking advantage of GPS technology and focusing research questions on movement behavior, wild turkey research can progress toward answering mechanistic questions regarding turkey habitat use. This shift in research focus will provide much‐needed information to managers that is currently lacking at both local and regional scales. © 2014 The Wildlife Society.